2021
DOI: 10.1140/epjc/s10052-020-08798-8
|View full text |Cite
|
Sign up to set email alerts
|

Off-diagonal cosmological solutions in emergent gravity theories and Grigory Perelman entropy for geometric flows

Abstract: We develop an approach to the theory of relativistic geometric flows and emergent gravity defined by entropy functionals and related statistical thermodynamics models. Nonholonomic deformations of G. Perelman’s functionals and related entropic values used for deriving relativistic geometric evolution flow equations. For self-similar configurations, such equations describe generalized Ricci solitons defining modified Einstein equations. We analyse possible connections between relativistic models of nonholonomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
(360 reference statements)
0
2
0
Order By: Relevance
“…The idea of a geometry having an entropy is counter-intuitive but is a consequence of the systematic consideration of the complementary nature of information and entropy that has become accepted since Shannon's seminal introduction of his "information entropy" [2]. We should note that the concept of a "geometric entropy" is already well accepted in quantum gravity contexts (see, for example, Vacaru et al [3]) but is not usually treated as an intrinsic property of geometrical structures, although perhaps Quevedo's "Geometrothermodynamics" [4] is an exception. We should also note not only that Wang et al [5] have recently specifically investigated the entropy production of certain natural growth processes but also that Pearson et al [6] have recently shown that a chronometer's accuracy is proportional to its entropy production.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of a geometry having an entropy is counter-intuitive but is a consequence of the systematic consideration of the complementary nature of information and entropy that has become accepted since Shannon's seminal introduction of his "information entropy" [2]. We should note that the concept of a "geometric entropy" is already well accepted in quantum gravity contexts (see, for example, Vacaru et al [3]) but is not usually treated as an intrinsic property of geometrical structures, although perhaps Quevedo's "Geometrothermodynamics" [4] is an exception. We should also note not only that Wang et al [5] have recently specifically investigated the entropy production of certain natural growth processes but also that Pearson et al [6] have recently shown that a chronometer's accuracy is proportional to its entropy production.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of a geometry having an entropy is counter-intuitive, but is a consequence of the systematic consideration of the complementary nature of information and entropy that has become accepted since Shannon's seminal introduction of his "information entropy" [2]. We should note that the concept of a "geometric entropy" is already well accepted in quantum gravity contexts (see for example Vacaru et al [3]), but is not usually treated as an intrinsic property of geometrical structure, although perhaps Quevedo's "Geometrothermodynamics" [4] is an exception. We should also note that Wang et al [5] have recently specifically investigated the entropy production of certain natural growth processes.…”
Section: Introductionmentioning
confidence: 99%